The Impact of Prolonged Chemotherapy to Surgery Interval and Neoadjuvant Radiotherapy on Pathological Complete Response and Overall Survival in Pancreatic Cancer Patients. (July 2020) - Azab, Basem; Macedo, Francisco Igor; Chang, David; Ripat, Caroline; Franceschi, Dido; Livingstone, Alan S; Yakoub, Danny
Background: We aimed to study the impact of neoadjuvant chemotherapy to surgery (NCT-S) interval and neoadjuvant radiotherapy (NRT) on pathological complete response (pCR) and overall survival (OS) in pancreatic cancer (pancreatic ductal adenocarcinoma [PDAC]). Methods: National Cancer Data Base (NCDB)–pancreatectomy patients who underwent NCT/NRT were included. The NCT-S interval was divided into time quintiles in weeks: 8 to 11, 12 to 14, 15 to 19, 20 to 29, and >29 weeks. Results: A total of 2093 patients with NCT were included with median follow-up of 74 months and 71% NRT. The pCR rate was 2.1% with higher median OS compared with non-pCR (41 vs 19 months, P = .03). The pCR rate increased with longer NCT-S interval (quintiles: 1%, 1.6%, 1.7%, 3%, and 6%, P < .001, respectively). In logistic regression, NRT (odds ratio [OR] = 2.5, 95% confidence interval [CI]: 1.1-6.1, P = .03) and NCT-S >29 weeks (OR = 6.1, 95% CI = 2.02-18.50, P < .001) were predictive of increased pCR. The prolonged NCT-S interval and pCR were independent predictors of OS, whereas NRT was not. Conclusions: Longer NCT-S interval and pCR were independent predictors of improved OS in patients with PDAC. The NRT predicted increased pCR but not OS.